2017
DOI: 10.1016/j.cell.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between Transcriptome Plasticity and Genome Evolution in Cephalopods

Abstract: Summary RNA editing, a post-transcriptional process, allows the diversification of proteomes beyond the genomic blueprint; however it is infrequently used among animals. Recent reports suggesting increased levels of RNA editing in squids thus raise the question of their nature and effects in these organisms. We here show that RNA editing is particularly common in behaviorally sophisticated coleoid cephalopods, with tens of thousands of evolutionarily conserved sites. Editing is enriched in the nervous system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
399
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(420 citation statements)
references
References 62 publications
20
399
1
Order By: Relevance
“…Positive selection: in a previous paper studying A-to-I RNA editing sites in cephalopods (Liscovitch-Brauer et al, 2017), the authors proved the positive selection on RNA editing events by showing that (a) The fraction of nonsynonymous editing events is higher than the genomic background; (b) The nonsynonymous editing levels are generally higher than the synonymous editing levels. In our study, we observed exactly the same pattern in Arabidopsis C-to-U RNA editome.…”
Section: Discussionmentioning
confidence: 98%
“…Positive selection: in a previous paper studying A-to-I RNA editing sites in cephalopods (Liscovitch-Brauer et al, 2017), the authors proved the positive selection on RNA editing events by showing that (a) The fraction of nonsynonymous editing events is higher than the genomic background; (b) The nonsynonymous editing levels are generally higher than the synonymous editing levels. In our study, we observed exactly the same pattern in Arabidopsis C-to-U RNA editome.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, a recent study found that unlike other bilaterians, coleoids, i.e. all cephalopods except for nautiluses, diversify their proteomes to a hitherto unknown extent by RNA editing (Liscovitch‐Brauer et al, ). This recoding appears to be evolutionarily conserved and adaptive among coleoids and may be one reason for their sophisticated cognitive abilities.…”
Section: Evodevo Genomes and The Diversification Of Molluscsmentioning
confidence: 99%
“…Co-transcriptional and post-transcriptional processing, such as RNA splicing and RNA editing, can alter the structure and sequence of RNAs, leading to different transcripts produced from the same DNA sequence. RNA editing can be defined as any site-specific alteration in RNA sequences, that include insertion or deletion of nucleotides and base conversion, and is an effective mechanism to modifying and enrich genetic information beyond the genetic code (Bahn et al, 2012;Li et al, 2011;Liscovitch-Brauer et al, 2017;Qulsum et al, 2019). The predominant type of RNA editing in animals is the conversion of adenosine (A) to inosine (I), catalyzed by a family of adenosine deaminases (ADARs) acting on double strand RNA (Nishikura, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another well documented type of RNA editing in humans is the deamination of cytidine leading to uridine (C-to-U), a RNA editing event catalyzed by the activation of APOBECs (Salter et al, 2016). However, it is still an enigma how the remaining ten nucleotide modifications found in humans (Li et al, 2011) and in cephalopods (Liscovitch-Brauer et al, 2017) transcriptomes can occur.…”
Section: Introductionmentioning
confidence: 99%